The Transnational Voices of Australia’s Migrant and Minority Press
XVII, 257 p. 5 illus.
Keywords: This edited collection is the first of two volumes and invites the reader to enter the diverse worlds of Australia’s migrant and minority communities through the latest research on the contemporary printed press, spanning the mid-nineteenth century to our current day. With a focus on the rare, radical and foreign-language print culture of multiple and frequently concurrent minority groups’ newspaper ventures, these volumes have two overarching aims: firstly to demonstrate how the local experiences and narratives of such communities are always forged and negotiated within a context of globalising forces – the global within the local; and secondly to enrich an understanding of the complexity of Australian ‘voices’ through this medium not only as a means for appreciating how the cultural heritage of such communities were sustained, but also for exploring their contributions to the wider society.